PEMBANGUNAN SMS GATEWAY HASIL PEMERIKSAAN UJIAN SEKOLAH BERBASIS WEB PADA MA BAHRUL ULUM SINGINGI - Ahmad Shodikun; Elgamar Syam (Universitas Islam Kuantan Singingi, 2018)
The problem that occurs in MA Bahrul Ulum Singingi i.e. on the submission of examination results of school examinations of the child can not get to the maximum by the parents. So delivery of information is only given to the students through notice board. The solutions provided by building information system with SMS Gateway facility as the conveyance of information. Systems development method using the waterfall method that consists of several stages, namely: analysis phase, design, coding, testing and support. The results obtained from this study is the SMS Gateway as a means to convey information by utilizing the computer as a tool to access the data. In conclusion this system can assist madrasah to provide information services to visitors.